Facilitating space charge directional separation for enhancing photocatalytic CO2 reduction over tetragonal BiVO4. Issue 18 (15th August 2022) - Dai, Dujuan; Wu, Yaqiang; Liu, Xiaolei; Xu, Yayang; Guo, Yuhao; Zhang, Qianqian; Wang, Zeyan; Zheng, Zhaoke; Liu, Yuanyuan; Cheng, Hefeng; Dai, Ying; Huang, Baibiao; et al.
Abstract : Spatially separated Ag/MnO x cocatalysts are selectively loaded on BiVO4 by a photo-deposition method. The synergistic effect of the dual cocatalysts enables the optimal photocatalytic activity of the sample to be 3.1 times higher than that of pristine BiVO4 . Abstract : The surface modification of dual cocatalysts on a photocatalyst is believed to effectively promote the separation of photogenerated carriers in the CO2 reduction reaction. Here, taking tetragonal BiVO4 with a strain effect as a substrate photocatalyst which has been proven to have enhanced reduction ability, BiVO4 modified with spatially separated dual cocatalysts Ag and MnO x is synthesized by a photo-deposition method for CO2 photoreduction without sacrificial agents. Compared with individual Ag–BiVO4 and MnO x –BiVO4, Ag–MnO x –BiVO4 has improved activity for reduction of CO2 to CO in a gas–solid system, which can be attributed to the spatially separated redox sites and enhanced photogenerated carrier separation efficiency. The optimal activity of the Ag–MnO x –BiVO4 sample is 3.1 times that of the original BiVO4 . In addition, PL and photoelectrochemical tests indicate that the dual cocatalysts can effectively inhibit carrier recombination and promote the photocatalytic reaction. This work reports a useful strategy for constructing a photocatalytic CO2 reduction system based on a BiVO4 photocatalyst.